Methods of Narrating Hadith - Wafik Azizah; Yossi Kurnia Yudatama (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The existence of Hadits is one of the source of law in Islam, where Hadits is the second source after the al-Qur’an. Efforts to transmit the Prophet’s Hadits also go through a process that starts from the generation of friends to the tabi’in generation and then to the tabi’in generation. In terms of narration, the narrator contributes fully to learning whether a hadist is good or not. There are two elements that must be know in the narration of hadist, namely Tahammul al-Hadist wa al-Ada’. From this, the author will discuss the methods must be used. In Tahammul al-Hadist wa al-Ada’ these methods are divided into eight methods, including: 1). Al-Sima’ min Lafzh al-syaykh, 2). Al-Qira’ah ‘ala al-syaykh, 3). Al-Ijazah, 4). Al-Munawalah, 5). Al-Mukatabah, 6). Al-I’lam, 7). Al-Washiyyah, dan yang terakhir 8). Al-Wijadah.